KETIMPANGAN PENDIDIKAN DI SULAWESI TENGGARA TAHUN 2019 DAN DETERMINANNYA - Dewi Cahaya Fitri; Yaya Setiadi (Politeknik Statistika STIS, 2020)
The issue of equitable education is one of the issues that needs to be taken seriously. This is in line with the fourth objective of the SDGs (Sustainable Development Goals) which proposes education in 2030, ensuring that all females and males complete free, equal and quality primary and secondary education, which leads to relevant learning outcomes and effective. Equitable education is related to educational inequality in an area. Inequality in education is one of the problems that must be resolved because, as stated in the UUD 1945 Pasal 31 that every citizen has the right to education. Unfortunately, the fulfillment of educational equality has still not been fully realised. This is shown by the high of Mean Years of Shooling (MYS) in Kendari which exceeds all MYS in districts/cities of DKI Jakarta which are not followed by other districts in Sulawesi Tenggara. This study aims to determine the description of educational inequality in Sulawesi Tenggara as measured by the 2019 Gini Coefficient of Education and its determinants with multiple linear regression methods. The results showed that the Literacy Rate significantly influenced Gini Coefficient of Education while the percentage of poor population and the percentage of the education budget did not significantly influence Gini Coefficient of Education in Sulawesi Tenggara 2019.